2015
DOI: 10.1007/s40618-015-0370-z
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the therapeutic spectrum of metformin: from diabetes to cancer

Abstract: If in vitro data appear solid, the results provided by in vivo studies are somehow controversial. In this view, larger studies are needed to fully elucidate the role of metformin on cancer development and progression, as well as the specific clinical settings in which metformin could become an anti-cancer drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 96 publications
0
32
0
6
Order By: Relevance
“…Cancer-free survival among patients using different treatment models. Differences between all groups were insignificant, p > 0.05 production and improving insulin sensitivity [4,16,17]. Moreover, it is possible that metformin may also play an additional immunomodulatory role [18].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Cancer-free survival among patients using different treatment models. Differences between all groups were insignificant, p > 0.05 production and improving insulin sensitivity [4,16,17]. Moreover, it is possible that metformin may also play an additional immunomodulatory role [18].…”
Section: Discussionmentioning
confidence: 91%
“…However, some authors did not found any protective effect of metformin on cancer development [12] or contests those associations due to the limitations of observational studies [13]. Nevertheless, a vast majority of evidence indicate reduced cancer risk among metformin users, which was confirmed in two large meta-analyses [4,14]. The anti-cancer action of metformin includes both direct and indirect effect on cancer cells growth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations